Thyroid Storm in A Patient with Graves’ Disease and Tubo-Ovarian Abscess: A Clinical Case Report - Ni Nyoman Gita Kharisma Dewi; Dewi Catur Wulandari (Indonesian Journal of Global Health Research, 2025)
Thyroid storm is a rare, life-threatening complication of thyrotoxicosis, involving multi-organ dysfunction. This study aims to identify risk factors for thyroid storm and evaluate effective management strategies to reduce mortality. This study is a descriptive case report. Data were collected through patient interviews, physical examinations, and supporting tests at Wangaya Hospital. The data were analyzed qualitatively and presented in a narrative format based on case report guidelines. This paper reports the case of a 24-year-old female with a history of hyperthyroidism on methimazole and an intrauterine device (IUD) presented with abdominal pain that started in the epigastric region and migrated to the lower quadrants. She developed ocular prominence, vomiting, palpitations, generalized weakness, and non-bloody diarrhea. She also experienced persistent lower abdominal pain (pain score: 6/10), dysuria, and fever. A Burch-Wartofsky Point Scale (BWPS) score > 45 confirmed thyroid storm. She was admitted to the ICU and treated with propylthiouracil (PTU), hydrocortisone, digoxin, propranolol, and antibiotics for suspected infection. Her condition improved, and she was discharged after seven days. Thyroid storm is commonly triggered by Graves' disease. The diagnosis is clinical, based on BWPS or the Japanese Thyroid Association criteria, especially in patients with a history of hyperthyroidism and a precipitating factor. PTU is preferred due to its rapid onset and ability to inhibit the conversion of T4-to-T3. Successful management of thyroid storm requires prompt, comprehensive therapy to suppress thyroid hormone levels and treat triggering factors such as infection.